Simulação da razão de carga de múons atmosféricos na escala TeV - Costa, Kelen Cristiane Noleto da (2011)
Several analysis can be performed using atmospheric muons produced in chain reactions caused by a cosmic ray particle. We can study the muon flux for different parameterizations of the atmosphere, the moon and sun shadowing effect, the muon charge ratio, etc. In this work, we are interested in the atmospheric muon charge ratio (rμ = Nμ+/Nμ−). This ratio has been observed by several experiments, for different energy ranges. The MINOS experiment has determined the muon charge ratio (rμ) in the GeV energy scale using the Near Detector and in the TeV energy scale using the Far Detector. This experiment has observed an increase of the muon charge ratio from 1.27 to 1.37 when the energy of the primary particle changed from ∼ 100 GeV to ∼ 1 TeV. This fact can be explained by the properties of the pions ( ) and the kaons (K). For higher energies, around 10 TeV, the decay of charming hadrons becomes important as a source of atmospheric leptons. Investigating the parameterization given by the Gaisser equation in order to study the intensity of positive and negative muons separately, it is possible to obtain the equation of the pion-kaon ( K) model. Using this model it was made an adjust with the of MINOS Near and Far Detector data, finding the f and fK parameters. These parameters are the fractions that contribute to the production of positive muons coming from de e K, respectively. The experimental values obtained were: f = 0.55 and fK = 0.70. In this work we simulated extensive air showers using the CORSIKA code. Different models that describe the hadronic interactions for high energy particles were used. Our goal was to verify if the models could reproduce the increase of muon charge ratio. This increase is associated with physics involving pion and kaon decays. We found the following parameters: f = 0.547 ± 0.003 and fK = 0.64 ± 0.02 for the QGSJET 01C model, f = 0.604 ± 0.003 and fK = 0.73 ± 0.02 for the SIBYLL model, f = 0.572 ± 0.003 and fK = 0.70 ± 0.02 for the VENUS model, f = 0.545 ± 0.004 and fK = 0.62 ± 0.03 for the QGSJETII model and f = 0.570 ± 0.003 and fK = 0.65 ± 0.02 for the DPMJET model. The increase of the muon charge ratio found in the MINOS data was 7.8%. In our simulation we found an increase of 3.2%, 8.3%, 5.7%, %4.0 and 2.5% for each one of the models, respectively. With these results, it was possible to observe that simulation models also show a significant increase of ratio, when we moved from scale GeV scale for TeV. And of course, this increase is characterized by properties of pions and kaons noting that physics is considered by the codes of models.